2020
DOI: 10.1080/0886022x.2020.1803086
|View full text |Cite
|
Sign up to set email alerts
|

Hypocomplementemia is associated with more severe renal disease and worse renal outcomes in patients with ANCA-associated vasculitis: a retrospective cohort study

Abstract: Background: The complement system has been recently proposed to play an important role in the pathogenesis of ANCA-associated vasculitis (AAV). This study evaluated the value of serum and kidney deposited C3 in predicting renal outcomes in AAV. Methods: This was a retrospective study of 47 patients with AAV, who were categorized according to their serum C3 levels as hypo-or normo-complementemic and to those with positive or negative kidney biopsy immunofluorescence (IF) for C3. Baseline characteristics as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
2
8
0
2
Order By: Relevance
“…Furthermore, hypocomplementemia was only detectable in a minor subset of ANCA GN and not correlated with renal or extrarenal AAV manifestations, in line with previous reports [26]. However, low levels of circulating C3c correlated with AKI severity in ANCA GN independent of systemic disease activity or extrarenal AAV manifestation, again in line with independent reports [27]. By systematic scoring of glomerular and tubulointerstitial lesions in association with circulating complement components C3c and C4, we here provide further insights into the mechanistic role of complement system activation in kidney injury to different renal compartments in ANCA GN.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, hypocomplementemia was only detectable in a minor subset of ANCA GN and not correlated with renal or extrarenal AAV manifestations, in line with previous reports [26]. However, low levels of circulating C3c correlated with AKI severity in ANCA GN independent of systemic disease activity or extrarenal AAV manifestation, again in line with independent reports [27]. By systematic scoring of glomerular and tubulointerstitial lesions in association with circulating complement components C3c and C4, we here provide further insights into the mechanistic role of complement system activation in kidney injury to different renal compartments in ANCA GN.…”
Section: Discussionsupporting
confidence: 89%
“…The major novel findings of this study, which included 142 Japanese patients with ANCA-GN, are as follows: glomerular complement deposition was detected in web 4C=FPO approximately 40% of the ANCA-GN kidney biopsy specimens by routine IF and C3-positive patients with ANCA-GN had both worse renal and overall survival at 5 years. The association between C3 deposition and poor renal and overall survival persisted after considering the previously reported predictors of renal outcomes in ANCA-GN 16,20,[23][24][25][26] and after changing the definition of outcomes or analyzing the patient subgroups. To the best of our knowledge, this is the largest study to date that investigated the glomerular deposition of Igs and complement using IF and the first study that evaluated the prognostic significance of C3 deposition.…”
Section: Discussionmentioning
confidence: 94%
“…11,13 Likewise, recent studies have reported that patients with AAV with low serum C3 level at diagnosis had poorer renal and overall survival rates. [14][15][16] Although data from humans have supported the complement activation involvement in human ANCA-GN, the clinicopathologic significance of complement deposition in patients with ANCA-GN is yet unclear. Most clinical studies 11,12,[14][15][16] investigating complement deposition in renal histopathology and/or serum complement level were limited because of small sample size or fewer kidney biopsy specimens.…”
mentioning
confidence: 99%
See 2 more Smart Citations